Interview with Professor Jeremy Spoon - Khattri, Man Bahadur; Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2025)
Professor Jeremy Spoon is a distinguished cultural anthropologist with deep familial roots in Ashkenazic Judaism and more distant Sephardic Jewish ancestry. Since 2006, he has conducted fieldwork in Nepal for his PhD and collaborated with the Central Department of Anthropology at Tribhuvan University, undertaking an in-depth study of the 2015 Gorkha earthquake. Prof. Spoon engages closely with community members and government agencies at various levels, ensuring his findings are validated and contextualized by study participants, decision-makers, local and national leaders, and other stakeholders before publication. Currently, he serves as a Research Professor of Anthropology at Portland State University in the United States. Since 2004, his research has centered on Indigenous and local communities across Nepal’s Himalayas, the Western United States, and other regions, including Detroit (Michigan, USA), Kenya, Tanzania, and Hawai‘i. He has mentored numerous graduate and undergraduate students through research projects, honors theses, and internships. His scholarship has been supported by the U.S. National Science Foundation, various U.S. federal agencies, Native American Tribal Nations, and non-profit organizations, demonstrating the broad significance and impact of his anthropological contributions. We extend our sincere thanks to Professor Jeremy Spoon for generously sharing insights into his journey, professional work, and ongoing responsibilities.